An OLTC-inverter coordinated voltage regulation method for distribution network with high penetration of PV generations. (December 2019) - Liu, Jiayan; Li, Yong; Rehtanz, Christian; Cao, Yijia; Qiao, Xuebo; Lin, Gang; Song, Yi; Sun, Chongbo
Highlights: Fuzzy controller is designed to operate OLTC and inverters, which does not require the accurate mathematical model between voltage and tap position. A power allocation optimization (PAO) method is proposed to coordinate the power output of inverters that can improve the overall utilization of PVDGs while ensure voltage stability. The voltage fluctuation problem in the multi-feeders distribution network is mitigated by coordinating the fuzzy and PAO modules. Abstract: The voltage fluctuation caused by the photovoltaic distributed generations (PVDGs) threatens distribution system stability. In a multiple feeder distribution network, the voltage fluctuation trends in different feeders will be varied because of the different types and capacities of distribution generators. In this paper, an on-load tap changer (OLTC) & inverter coordinated regulation method is proposed. The fuzzy controller is implemented to coordinate the OLTC and power allocation optimization (PAO) Module. The PAO Module coordinates all inverters on a feeder to maintain terminal voltage of this feeder in rated range while maximizing the active power output of the inverters. By means of the state estimation, the fuzzy logic gathers voltage information from different feeder terminals, to decide whether to maintain voltage stability via adjusting OLTC or PAOs. Thus, the efficiency of PV generations can be improved greatly. A typical distribution network with high penetration of PV distributed generations is built to validate the results.